Relasi Sang Ego dan Sang Liyan dalam Tjerita Njai Dasima Soewatoe Koeban Dari Pada Pemboedjoek : Kajian Feminis Pascakolonial - Dwi Susanto (KAJIAN SASTRA, 2008)
This ND text tells complexity of matters on the relation betweenthe ego and the other. The relation is suspected for annexation.Elucidation of the relation shows that the ego annexes the other many times over. Identity games, role obscurity, power loss and good deeds of the ego lead the main body and mind, is used as a device and politics by the ego to destroy, disdain and civilize the other. The ND text also deconstructs or demolishes its'narrative building' and textual strategy. It is evident when Mark Buyung as a tangent area breaks down ond destroys various discourse and the ego construction to annex the other (indigenous). Nyai Dasimo is a representation and symbol of a colony, women and colonial power so os to become a prey for the ego and the other, her legal owner.